2014
DOI: 10.1038/npp.2014.9
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and Metabolic Dysregulation and the 2-Year Course of Depressive Disorders in Antidepressant Users

Abstract: Scarce evidence suggests that inflammatory and metabolic dysregulation predicts poor response to antidepressants, which could result in worse depression outcome. This study prospectively examined whether inflammatory and metabolic dysregulation predicted the 2-year course of depressive disorders among antidepressant users. Data were from the Netherlands Study of Depression and Anxiety, including 315 persons (18-65 years) with a current depressive disorder (major depressive disorder, dysthymia) at baseline acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 50 publications
(56 reference statements)
6
86
2
1
Order By: Relevance
“…The results from this study were also in accordance with a report by Vogelzangs et al (Vogelzangs et al, 2014). They prospectively examined whether inflammatory and metabolic dysregulation predicted outcomes in 315 patients with depressive disorders receiving antidepressant treatment for 2 years.…”
Section: Comparison With Previous Studiessupporting
confidence: 89%
See 2 more Smart Citations
“…The results from this study were also in accordance with a report by Vogelzangs et al (Vogelzangs et al, 2014). They prospectively examined whether inflammatory and metabolic dysregulation predicted outcomes in 315 patients with depressive disorders receiving antidepressant treatment for 2 years.…”
Section: Comparison With Previous Studiessupporting
confidence: 89%
“…Because visceral adiposity is associated with insulin resistance, dyslipidemia, and systemic inflammation (Lee and Pratley, 2005), the lower predictive power of BMI for visceral adiposity in men could mask the effect of obesity and allow observation of only the effect of metabolic condition on insufficient treatment response. Moreover, Asian men possess a greater amount of visceral adipose tissue than do women at the same level of BMI and are therefore more likely to experience related inflammation (Vogelzangs et al, 2014).…”
Section: The Relationships Between Metabolic Abnormalities and Antidementioning
confidence: 99%
See 1 more Smart Citation
“…Although an earlier study by Berk et al failed to demonstrate overall significant beneficial effects of NAC supplementation to regular antidepressant treatment at 12-week end point [10], a secondary analysis suggested a positive effect of NAC in patients with more severe depression. In contrast to the present study inflammatory activity was not specifically assessed in the study by Berk et al [10] but work from our own group has shown that increased inflammatory activity is related to non-response in depressed patients treated with antidepressants [7]. By sharpening the inclusion criteria in the present study, we expect to reduce heterogeneity of the patient sample, diminish possible confounding effects by other medications and develop a tailored intervention for patients with mood disorder with inflammatory dysregulation who have do not respond to regular phases of antidepressant treatment.…”
Section: Discussionmentioning
confidence: 69%
“…However, seniors are often with large degree of medical co-morbidity, especially vascular diseases, or with much unfavorable profile of inflammatory and metabolic dysregulations, which may contribute to the development of depression in late life [5][6][7][8][9][10]; while antidepressants use are often associated with weight gain and metabolic abnormalities [11][12][13]. As drug therapy is often selected as a primary mode of management in depression and the antidepressants now rank as the most frequently dispensed prescription medication in the US [14], the risk for metabolic syndrome (MS) among seniors is particularly a concern.…”
Section: Introductionmentioning
confidence: 99%